Analisis Perspektif Polycentric Governance Pada Pemerataan Akses Pendidikan Inklusif DiKota Yogyakarta - Sazeta, Mirza; Sutan, Arissy Jorgi; Syahrier, Fajar Alan; Ishak, Ishak (Jurnal Administrasi Politik dan Sosial, 2025)
This study aims to see the equality related to access to inclusive education in Yogyakarta City from the perspective of Polycentric Governance. Inclusive education in Yogyakarta City is integral to the government's efforts to realize equal education rightsfor all children, including children with special needs (ABK). Qualitative Descriptive Analysis using Qualitative Data Analysis Software (Q-DAS) is the research method. This study analyzes the application of polycentric governance in the accessibility of inclusive education in Yogyakarta City through three approaches: analysis of main indicators, identification of dominant themes, and relationships between indicators using NVivo 12Plus. The results show multi-actor involvement (37.5%) as the most dominant indicator, followed by coordination between institutions (33.33%) and decentralization of local innovation (29.17%). The main themes that emerged were "education," "inclusive," and "disability." The relationship analysis shows a high correlation between indicators, especially between institutional coordination and local innovation (0.91), confirming the importance of cross-actor collaboration in supporting an adaptive and sustainable inclusive education system.